Penyuluhan Perawatan Bayi Berat Badan Lahir Rendah (BBLR) untuk Meningkatkan Kapasitas Ibu Nifas dalam Perawatan Neonatal - Dewi Dewi; Sumarmi Sumarmi; Hamka Hamka; Hermadin Hermadin; Riska Nuryana (Jurnal Pengabdian Bidang Kesehatan, 2025)
Background: Low Birth Weight Infants (LBW), defined as babies born weighing less than 2,500 grams, are one of the leading causes of neonatal mortality in Indonesia. The lack of postpartum mothers’ knowledge about LBW care contributes to the low survival rate of these infants. WHO data (2022) shows that 15% of babies worldwide are born with LBW, while in Indonesia, the figure reaches 7.1% (Ministry of Health RI, 2023). Objective: This activity aims to enhance postpartum mothers' capacity in caring for LBW infants through structured and practice-based health education. Methods: The community service was conducted on May 7, 2025, at RSUD Padjonga Dg Ngalle, Takalar. The method included a pre-test, delivery of educational material, practical sessions, and a post-test. Thirty postpartum mothers participated under the guidance of lecturers and health professionals. Evaluation focused on participants' knowledge, practical skills, and behavioral changes.Results: The results showed a significant increase in participants’ knowledge (from 26.7% to 83.3% answering more than 80% of the post-test questions correctly). Around 90% of participants were able to correctly perform kangaroo mother care techniques. Moreover, 85% of participants reported increased confidence in caring for their LBW babies at home after the session. Conclusion: This health education activity was effective in improving the knowledge, skills, and confidence of postpartum mothers in caring for LBW infants. The program supports efforts to reduce neonatal mortality and empowers mothers as the primary caregivers in home-based neonatal care.